Lumbar disc arthroplasty with Maverick disc versus stand-alone interbody fusion: a prospective, randomized, controlled, multicenter investigational device exemption trial - Gornet, Matthew F; Burkus, J Kenneth; Dryer, Randall F; Peloza, John H (Spine (Philadelphia, Pa. 1976), 2011)
Randomized, controlled, multicenter, investigational device exemption trial. To investigate the safety and effectiveness of the first two-piece, metal-on-metal lumbar disc prosthesis for treating patients with single-level degenerative disc disease. For patients with degenerative disc disease unresponsive to conservative measures, lumbar disc arthroplasty provides an alternative to fusion designed to relieve persistent discogenic pain and maintain motion. After 2:1 randomization, 577 patients were treated in either the investigational group (405), receiving lumbar disc arthroplasty, or the control group (172), receiving anterior lumbar interbody fusion. Patients were evaluated preoperatively, at surgery/discharge, and at 1.5, 3, 6, 12, and 24 months after surgery. The primary study endpoint was overall success, a composite measure of safety and effectiveness as recommended by the Food and Drug Administration and defined in the protocol. Both treatment groups demonstrated significant improvements compared with preoperative status. The investigational group had statistically superior outcomes (P < 0.05) at all postoperative evaluations in Oswestry Disability Index, back pain, and Short Form-36 Physical Component Summary scores as well as patient satisfaction. Investigational patients had longer surgical times (P < 0.001) and greater blood loss (P < 0.001) than did control patients; however, hospitalization stays were similar for both groups. Investigational patients had fewer implant or implant/surgical procedure-related adverse events (P < 0.001). Return-to-work intervals were reduced for investigational patients. Disc height and segmental angular motion were maintained throughout the study in the investigational group. In the investigational group, overall success superiority was found when compared to the control group as defined by the Food and Drug Administration Investigational Device Exemption protocol. The investigational group consistently demonstrated statistical superiority versus fusion on key clinical outcomes including improved physical function, reduced pain, and earlier return to work.